Inhalable nanovesicles loaded with a STING agonist enhance CAR-T cell activity against solid tumors in the lung - Tianchuan Zhu; Yuchen Xiao; Zhenxing Chen; Hanxi Ding; Shoudeng Chen; Guanmin Jiang; Xi Huang (Nature Communications)
Abstract Suppression of chimeric antigen receptor-modified T (CAR-T) cells by the immunosuppressive tumor microenvironment remains a major barrier to their efficacy against solid tumors. To address this, we develop an anti-PD-L1-expressing nanovesicle loaded with the STING agonist cGAMP (aPD-L1 NVs@cGAMP) to remodel the tumor microenvironment and thereby enhance CAR-T cell activity. Following pulmonary delivery, the nanovesicles rapidly accumulate in the lung and selectively deliver STING agonists to PD-L1-overexpressing cells via the PD-1/PD-L1 interaction. This targeted delivery effectively avoids the systemic inflammation and poor cellular uptake that plague free STING agonists. Internalized STING agonists trigger STING signaling and induce interferon responses, which diminish immunosuppressive cell populations such as myeloid-derived suppressor cells in the tumor microenvironment and promote CAR-T cell infiltration. Importantly, the anti-PD-L1 single chain variable fragment on the nanovesicle surface blocks PD-L1 upregulation induced by STING agonists and prevents CAR-T cell exhaustion. In both orthotopic lung cancer and lung metastasis model, combined therapy with CAR-T cells and aPD-L1 NVs@cGAMP potently inhibits tumor growth and prevents recurrence. Therefore, aPD-L1 NVs@cGAMP is expected to serve as an effective CAR-T cell enhancer to improve the efficacy of CAR-T cells against solid tumors.